Rivaroxaban for Venous Thromboembolism (VTE) in Paediatric Patients: an institutional retrospective observational study from the Low/Middle Income setting in Pakistan - Mahmood, Aimen; Moiz, Bushra; Fadoo, Zehra; Belgaumi, Asim; Mushtaq, Naureen; Altaf, Sadaf (Journal of the Pakistan Medical Association, 2025)
Objectives: To evaluate bleeding events, mortality, recurrence and prescribing practices in paediatric and adolescent patients of venous thromboembolism using direct acting oral anticoagulants (DOACs). Method: The descriptive, retrospective study was conducted from November 2021 to May 2022 at the Aga Khan University Hospital and comprised data from 2017 to 2021 of patients from birth to 18 years who received DOACs for prophylaxis or treatment purposes of venous thromboembolism. Data was analysed using STATA MP.15. Results: Of the 45 patients, 37(82.2%) were males and 8(17.8%) were females. The overall median age was 16 years (interquartile range: 12.5-18 years). Of the total, 33(73.3%) patients were treated for acute venous thromboembolism, while 12(26.7%) received anticoagulants as prophylaxis. Complete thrombus resolution was achieved in 15(45.5%) patients, partial resolution in 3 (9.1%), and no resolution in 4(12.1%). Recurrence of venous thromboembolism occurred in 2(6%) patients. Enoxaparin was prescribed in 24(53.3%) cases, rivaroxaban in 14(31.1%) and heparin in 7(15.6%). There were 13(28.9%) deaths in the cohort. Conclusion: Rivaroxaban may be safe in the management of paediatric venous thromboembolism, with no major bleeding complications observed in our study. Key Words: Rivaroxaban, Direct oral anticoagulants, Paediatric, Low middle-income country.